EFFECT OF PLANT SOURCE ORGANIC FERTILIZERS ON YIELD AND IT'S COMPONENTS OF LINSEED CULTIVARS - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A field trials was carried out during winter season of 2017-2018 and 2018-2019 at Field Crops Department - College of Agricultural Engineering Sciences - University of Baghdad / Jadriyah to study the effect of organic fertilizers of plant source (compost) on yield and it's components of linseed cultivars. Randomized complete block design (RCBD) arranged according to split plots used with three replicates. The trials included four weed sources organic fertilizer {Malva rotundifolia L., Eichhronia crassipes (Mart) Solms, Glycyrrhiza glabara L. and Silybum marianum L.} and NPK chemical fertilizer (90 Kg N ha-1, 120 Kg P ha-1 and 80 Kg K ha-1) in addition to control treatment (without fertilizer) within main plots and three linseed cultivars (Syrian, Egyptian and Iraqi local) within sub plots. The results showed that the Syrian cv. produced  the highest number of capsules 106.67 and 103.75 capsule plant-1, number of seeds 8.03 and 8.33 seed capsule-1, seed yield 1.03 and 1.12 mton ha-1, biological yield 4.24 and 4.50 mton ha-1 and harvest index 24.21 and 24.82%, while the Egyptian cv. gave highest means of 1000 seeds weight 6.73 and 7.22 g for the two seasons, respectively. The fertilizer treatments significantly affected on the all studied characters. The plant at the NPK treatment produced the highest number of capsules 105.48 and 99.74 capsule plant-1, number of seeds 7.89 and 7.95 seed capsule-1 without significant differences on the G. glabara L. treatment which was superior in the seed yield 1.04 and 1.03 mton ha-1, biological yield 4.18 and 4.32 mton ha-1 and harvest index 24.57 and 23.65% without significant differences with NPK treatment for the two seasons, respectively. The interaction between the two factors had significant effect on all characters except 1000 seeds weight at first season.